A numerical model for the performance assessment of hydrophobic meshes used for oil spill recovery. (February 2018) - Coene, Emilie; Silva, Orlando; Molinero, Jorge
Highlights: A model is proposed for oil-water separation with hydrophobic meshes. The model is based on two-phase flow in porous media. Oil recovery and water breakthrough depend strongly on the fluid column height. Mesh materials and dimensions also affect wettability and oil recovery efficiency. A mesh performance curve can be used for industrial designing purposes. Abstract: Accidental oil spills in the ocean have a big impact on aquatic environments and human activities, and one of the most promising clean-up techniques is the use of hydrophobic and oleophilic meshes. It is important to understand the underlying physics of these meshes and their behavior under different conditions. Here, a mesh is conceptualized as an equivalent porous medium where the oil recovery and water breakthrough depend on the fluid column height and material properties. A model of two-phase flow through the mesh was implemented in COMSOL Multiphysics ® . Hydrophobicity, contact angles and surface tension effects are considered through a capillary retention curve, while flow properties are represented by permeability functions. The model was verified and tested with existing experimental data. It constitutes a powerful tool for future research and optimization of environmental solutions based on hydrophobic and oleophilic meshes. Graphical abstract: Image, graphical abstract